Clinical profile and outcome of neonates admitted during summer months with dehydration and hypernatremia in tertiary care hospital of central Gujarat, India - Shah, Rinki H.; Javadekar, Bakul B. (International Journal of Contemporary Pediatrics, 2018)
Background: Dehydration and hypernatremia amongst exclusively breast fed neonates due to inadequate breast feeding or due to less feeding is a potentially devastating condition, and its incidence rate increases during hot environment especially during summer months. We conducted this study to identify possible etiology behind dehydration and hypernatremia among healthy newborn. Methods: Authors retrospectively studied from available records from our Extramural NICU for months of March, April, and May 2017. Inclusion criteria for study were 1) Neonates with signs and symptoms of dehydration, 2) exclusively breast fed newborn. Those with congenital malformations, very low birth weight and perinatal asphyxia were excluded from the study. Results: Total NICU admissions were 434 during these months, and 28 patients we received with dehydration and 21 patients out of 28 had hypernatremia. Incidence rate of dehydration was 6.45%. Almost all the patients had altered renal functions at the time of admission, which became normal before discharge. 4 patients had culture proven sepsis. 2 patients died out of 28 patients. 26 patients out of 28 recovered completely and discharged. Conclusions: Dehydration and hypernatremia is preventable and treatable condition. All the mothers needs to taught correct feeding method like proper position and attachment of feeding. Signs of dehydration must be explained to mother as well as close relatives. Follow up visits should be ensured and check for weight is must. Not to encourage mother to give any other feed apart from exclusive breast feeding for first 6 months and even during summer months.